INDIVIDUAL THERAPY (COUNSELING) FOR CHANGES IN SELF-ESTEEM OF PARENTS WHO HAVE CHILDREN WITH SPECIAL NEEDS - Terok, Maria; Malonda, Grazyela (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
ackground: The condition of children with special needs is a separate problem for parents, causing the need for special handling in various ways. These problems can have an impact on parental self-esteem. Individual therapy is therapy that is carried out individually to discuss individual problems and overcome problems faced by individuals. Individual therapy in the form of counseling can help change the self-esteem of parents who have children with special needs. Purpose: to determine the effect of individual therapy on changes in self-esteem of parents who have children with special needs. Method: the research used is a literature review research using the results of previous research and also using textbooks, which are accessed through PubMed, Sage and Google Scholar, on a national and international basis. The journal requirements you are looking for are from 2015 to 2020 and 6 articles that meet the criteria. Results: there are 6 articles that meet the inclusion criteria and are appropriate according to the topic, regarding the effect of individual therapy (counseling) on ​​increasing the self-esteem of parents who have children with special needs. individual therapy (counseling) using CBT (Cognitive Behavior Therapy) techniques has an effect on increasing the self-esteem of parents who have children with special needs Suggestion: can be used as a reference to increase insight, develop knowledge and can be used as material in the learning and teaching process.